The Perception of Malaysian ESL Tertiary Level Students on the IELTS Test - Zahari, Dhiya Amalina; Dhayaalan, Jeremiah Dhayaalan Jackson (Asian Journal of Education and Training, 2016)
Currently, the most acknowledged test to qualify for overseas universities is the IELTS test which is referred to as the International English Language Testing System. It is implemented as an accreditation tool and is believed to be a reputable and trustworthy tool of language competence by tertiary institutions which employ its use. Regardless of the current attention received by IELTS today, the views and opinions of candidates sitting for the test have seldom been looked into. Thus, this research is focused on examining the perception of Kolej MARA Banting candidates on the IELTS test. Consequently, a 9 item questionnaire on perception was given to 20 participants prior to and after sitting for the IELTS test. The data gathered was evaluated using t- test analysis to investigate the comparative differences among the learners’ perception prior to and after sitting for the test. Results proclaimed that candidates obtained a notably more positive perception after the test. Hence, some implications are made for all stakeholders especially those learners who are planning to take the test, educational organizations that are overseeing IELTS preparatory programs, educators who aspire to train candidates in such programs and administers of the test.